The Relationship of Perceived Stress, Emotional Intelligence and Resilience with Subjective Well Being among Nurses - Muddsar Hameed; Mahekamil Latif Abbasi; Zarsha Khan; Tehreem Islam; Museera Aymen (Journal of Management Practices, Humanities and Social Sciences, 2023)
The study investigates the association between nurses' subjective well-being, emotional intelligence, resilience, and perceived stress. The purpose of the study is to better understand how nurses' subjective well-being effected by stress, emotional intelligence and resilience. The study conducted in Islamabad and Rawalpindi. The data was collected from public and private hospital of Islamabad. Study started in November 2022 and end in June 2023. Correlational research design were used A broad collection of nurses from various healthcare settings were gathered with a sample size N = 300 (calculated by Rao soft), with ages ranging from (20-50 years). The background details of nurses were collected with the use of demographic form. The Perceived Stress Scale (PSS), Schutte Self-Report Emotional Intelligence Test, Brief Resilience Scale (BRS) and Satisfaction with Life Scale (SWLS) were used. The results revealed a significant relationship between perceived stress, emotional intelligence, and job experience with the subjective well-being of nurses, predicting the role of perceived stress, emotional intelligence, resilience, and job experience on the well-being of nurses. The values (β = .41, p = 0.00 showed a 41% variance (R2 = 0.41). The research on the connections between perceived stress, emotional intelligence, resilience, and subjective well-being among nurses, in particular, offers important new understandings of the variables affecting the general well-being of this crucial healthcare profession.